Hydrogen production from CO2 reforming of methane using zirconia supported nickel catalyst. Issue 17 (7th April 2022) - Kurdi, Abdulrahman N.; Ibrahim, Ahmed A.; Al-Fatesh, Ahmed S.; Alquraini, Abdullah A.; Abasaeed, Ahmed E.; Fakeeha, Anis H.
Abstract : The use of hydrogen as an alternative fuel is an attractive and promising technology as it contributes to the reduction of environmentally harmful gases. Abstract : The use of hydrogen as an alternative fuel is an attractive and promising technology as it contributes to the reduction of environmentally harmful gases. Finding environmentally friendly cheap active metal-based catalysts for H2 rich syngas via dry reforming of methane (DRM) for industrial applications has posed a challenge. In this paper, H2 production via CO2 reforming of methane was investigated over 5Ni/ZrO2 catalysts. The catalytic performance of all prepared catalysts was evaluated in a microtubular fixed bed reactor under similar reaction conditions ( i.e., activation temperature at 700 °C, feed flow rate of 70 ml min −1, reaction temperature 700 °C for 440 min reaction time) of CO2 reforming of methane. Different characterization techniques such as; BET, CO2 -TPD, TGA, XRPD, Raman, and TEM, were used. The study of the textural properties of catalysts established that the BET of pristine catalyst (5NiZr) was enhanced by the addition of modifiers and promoters. A bimodal TPR distribution in the reduction temperature range of 250–550 °C was recorded. In the CO2 -TPD analysis, the strength of basicity came in this order: 5Ni15YZr > 5Ni10YZr > 5Ni5YZr > 5NiZr > 5Ni20YZr. The investigation of catalyst modifiers (MgO and Y2 O3 ) resulted in the Y2 O3 modifier improving the activity and catalytic performance better than MgO, which generated a hydrogen yield of 22%. 15% Y2 O3 modifier loading gave the highest H2 yield 53% in the phase of different loadings of yttria. The study of the influence of promoters (Cs, Ga, and Sr) revealed that the catalytic performance of 5Ni15YZr catalysts promoted with Sr towards the H2 yield enhanced the activity to 62%. The promoted catalysts displayed lower carbon deposition compared to the unpromoted catalyst, which provided 25.6 wt% weight loss.